Strengthening teachers classroom assessment practices for innovative learning and 21st century skills (2020)
Information gathering on students 'performance is a means to assist them to make progress in their educational career and have sound knowledge of concepts and standards. Every activity that goes on between the teacher and the student in the classroom setting is regarded as an assessment which aims at determining the extent to which teaching-learning process had taken place. Strengthening classroom assessments can raise students' overall achievement and can be used to diagnose low-achieving students. Twenty-first century skills require teachers to be innovative and have holistic approach that did not focus only what learners have learnt but also how it was learnt. It is expected that data collected by assessing students will not only be useful for measuring learners' progress only but also for improving their own instructional practice. The current practice of assessment lacks the involvement of learners as a result of teachers' low ability to carry out objective assessment. In the twenty-first century, it is inevitable for teachers to make learning easier and more effective for students. These demands building teachers' capacity in best practices in classroom assessment is inevitable. Effective use of any of the suggested approaches in this paper is capable of strengthening teachers' classroom assessment practices for innovative learning and sustainable development.